Mythical Concept of Karmayoga in Arun Joshi’s The Foreigner - Dharmrajsinh Pravinsinh Chauhan (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The publication of The Foreigner in 1968 marked Arun Joshi's debut on the Indian English literary terrain. Joshi attempts to demonstrate that people are still willing to embrace the mythical concept of Karmayoga, which is depicted in the second and third chapters of the Gita, in the construction of the foreigner's primary subject, which is devotion to life and practice rather than passive detachment. In reality, he oscillates between detachment and attachment. Joshi is profoundly influenced by the Bhagawad Gita in the formulation and resolution of this problem, such that the novel is unjustifiably interpreted as an illustration of Lord Krishna's Karmik Principle in chapters II-III of the Gita. The expatriate is on the path from his estrangement from the world to his involvement with Sindi Oberoi, the protagonist. Sincerity and candour characterize Sindi's description of his pursuit of the meaning and purpose of existence. The protagonists attempt to surmount their inner turmoil with the assistance of mythology. The present paper examines how the Hindu philosophy associated with the Bhagavad Gita aids the characters in overcoming life's challenges. An effort has been made to investigate the theistic and atheistic perspectives of characters, as well as how beliefs aid in their survival.